PERAN ORANG TUA DALAM MENINGKATKAN KEPERCAYAAN DIRI ANAK USIA DINI MELALUI CERITA RAKYAT LUTUNG KASARUNG - Samaniah, Sopahatus; Rukanda, Nandang (IKIP Siliwangi, 2025)
The self-confidence of young children should be approached wisely. Globalization is not a reason to undermine the noble values of Indonesian culture ingrained in Pancasila. In an increasingly liberal era of globalization, indigenous intellectual values must be nurtured. One of the local cultural products is the folk tale of Kebumen from Lutung Kasarung, Central Java. The aim of this study is to discover information and strengthen the faith of children by narrating the values contained in the folk tale of Lutung Kasarung, as well as to immerse in this ancient story to preserve Indonesian culture from the influence of other foreign cultures. From the research findings on this topic, it can be concluded that when folk tales are read to children, it contributes to enhancing their self-confidence, as the values embedded in each tale can have positive impacts. A child absorbs its essence better when you consider each folk tale individually. As an alternative, this action aims to preserve the heritage of local traditions and culture.